Pengaruh Berat Katalis La/ZnO Dan Waktu Reaksi Terhadap Pembuatan Biodiesel Dari Crude Palm Oil - Khairul, Anapuja; Bahri, Syaiful; Wisrayetti, Wisrayetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Domestic demand for petroleum is increasing while Indonesia's oil reserves are running low leading to high world oil prices. To overcome this it is necessary to develop alternative renewable energy derived from vegetable oil, one of which is biodiesel. Purposes of this research were to produce biodiesel from CPO, having study the effect of different weight of the catalyst and reaction time on process of palm oil biodiesel, determine the characteristics of catalyst La/ZnO. The La/ZnO catalyst is made by impregnate 3 % La into ZnO, then dried using oven and calcination, oxidation and reduction. Production of biodiesel is carried out through two stages: esterification and transesterification. The highest yield resulted on La/ZnO catalyst weight 1% which is 92.46%. Production biodiesel from CPO using La/ZnO catalyst produces biodiesel which can be used as alternative energy, catalyst weight and reaction time are directly proportional to the yield of biodiesel from CPO, La/ZnO catalysts have good selectivity against biodiesel from CPO.Keywords: biodiesel, CPO, La/ZnO, transesterification